Tree-ring width and variation of wood density in Fraxinus excelsior L. and Quercus robur L. growing in floodplain forests - Giagli, Kyriaki; Baar, Jan; Fajstavr, Marek; Gryc, Vladimír; Vavrčík, Hanuš (North Carolina State University, 2018)
Oven-dry wood density variations are reported for European ash (Fraxinus excelsior L.) and English oak (Quercus robur L.) trees growing in floodplain mixed forests in South Moravia, Czech Republic. Two sites with different water regime conditions were selected along the Dyje (site A) and the Morava (site B) Rivers. In total, 20 dominant, healthy trees were chosen to determine the tree-ring structure and the oven-dry wood density (ρ0) along the radius of the stem cross section. The tree-ring width followed the common trend of a general decline as the trees aged. After removing the age influence, significant differences were observed in the tree-ring structure, recorded several years after water regime treatments. The European ash and the English oak ρ0 were found to be 677.3 kgBULLET OPERATORm-3 and 618.2 kgBULLET OPERATORm-3, respectively, significantly differing between the sites, for both species. High variability of ρ0 was also noticed along the stem radius in both species and sites.
Keywords: European ash; English oak; Floodplain forests; Oven-dry density; Tree rings; Variability